Review of Mindset - George M Jacobs (International Journal of Pedagogy and Teacher Education, 2019)
Educators can benefit from occasionally stepping outside our profession to look for new ideas. Mindset: Changing the Way You Think to Fulfil Your Potential is a book that was written by a well-regarded psychology professor and has sold more than a million copies. The book’s central premise is that people tend toward one of two mindsets: a fixed mindset, which sees ability as inborn and largely unmodifiable; and a growth mindset, which sees ability as something people can develop by making persistent effort and learning new strategies. The present book review begins with explaining the two mindsets. Then, questions about mindset are answered. Next, in the review’s longest portions, suggestions from the book which might be useful for teachers are shared. These suggestions may help students become more successful learners, not to mention better people overall. Finally, the reviewer recommends that when the author and her colleagues do further work on mindsets, they might wish to examine mindsets through a more collective, sociological perspective than from an individual, psychological view.